Increasing screening frequency in men who have sex with men: impact of guidance on risk profiling on workload and earlier diagnosis of sexually transmitted infection and HIV. (August 2013) - Baker, A; Fleury, C; Clarke, E; Foley, E; Samraj, S; Rowen, D; Patel, R
Summary: Increasing screening frequency in men who have sex with men (MSM) engaging in high-risk behaviours can reduce prevalence of sexually transmitted infections (STIs). This evaluation investigated the impact of applying stricter screening guidelines for MSM on service workload and earlier STI diagnoses. A validated risk assessment tool (RAT) was distributed to MSM attending a level 3 sexual health service over three months. Australian screening guidelines were applied to the data to identify MSM requiring more frequent screening and data projected to the larger MSM population. The RAT identified a 2–5-fold increase in the number of STI and HIV screenings required based on six- and three-monthly screening intervals, respectively, in the MSM cohort. When screening intervals are reduced from three-monthly to six-monthly there is a potential loss of 66.7% of earlier HIV diagnoses. The use of RATs will increase workload in sexual health services, but potentially diagnose a large proportion of disease earlier.